The influence of carbon sources on the production of siderophores from the fluorescent pseudomonad bacteria - V Violita; Irma Laelani Eka Putri; Ansel Nastika (Bioscience, 2018)
Land kangkung (Ipomoea reptans Poir.) is one of the types of kangkung plants that are quite easy to be cultivated but because of the narrowness of urban agriculture land, it is difficult for the people to cultivate kangkung. Now there are one alternatives to exploit narrow land as an effort to develop organic farming, that is by farming in a hydroponic way. This study aims to determine the effect of liquid organic fertilizers made from Sargassum sp. on the growth of land kangkung (Ipomoea reptans Poir.) with hydroponic technique. This research is an experimental research conducted in December 2017 until April 2018, housed in research laboratory and home wire Biology FMIPA UNP. This study used Completely Randomized Design (RAL) 6 treatments and 4 replications. The main observation parameters include Plant height (cm), Number of Leaves, Leaf Area (cm2), Plant Wet Weight (g) and Dry Weight Plant (g). The data were analyzed using Analysis of Variance (ANOVA) test and DNMRT further test at 5% level. The results showed that liquid organic fertilizer made  from  Sargassum sp. had no signifficant effect on plant height, surface area, number of leaves, wet weight and dry weight of land  kangkung (Ipomoea reptans Poir.)